Ventral Primary Hernia with Liver Content - Inès Dufour; Lancelot Marique; Thomas Valembois; Arnaud Ghilain; Gabriela Beniuga; Nicolas Tinton; Sabrina Urso; Benoît Colinet (Case Reports in Surgery)
Background. Herniation of the liver through the anterior abdominal wall is an extremely rare phenomenon. Most cases occur within an incisional hernia (mostly upper abdomen surgery or cardiac surgery). Only two reports mentioned liver herniation without previous abdominal incision. Case Presentation. We report the case of a 70-year-old woman presenting an epigastric swelling. Radiological findings showed a liver herniation in a primary ventral hernia. This case is the first to have been described requiring semiurgent hernia repair associated with partial liver resection. Conclusion. This case is, to the best of our knowledge, the first case of primary ventral hernia with liver content necessitating wedge resection of the left liver lobe.